2009
DOI: 10.1007/s11095-009-9973-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Evaluation of Targeting Potential of Amphotericin B-Loaded Engineered PLGA Nanoparticles

Abstract: The results suggest that engineering of nanoparticles could lead to development of efficient carrier for macrophage targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…[5][6][7] In addition, the stability, tissue permeability, degradation rate, and toxicity of NPs themselves are also concerns in this field. [8][9][10] The recently developed diblock copolymer D-α-tocopheryl polyethylene glycol 1000 succinate-b-poly(ε-caprolactone-ran-glycolide) (TPGS-b-(PCL-ran-PGA) [hereafter, referred to as PLGA-TPGS]) has received special attention as a promising antimicrobial agent, due to its good biocompatibility and biodegradability. 7 Therefore, the synthesis of uniform PLGA-TPGS copolymer NPs (PLGA-TPGS NPs) with specific requirements in terms of size, shape, and physical and chemical properties is of great interest in the development of new drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In addition, the stability, tissue permeability, degradation rate, and toxicity of NPs themselves are also concerns in this field. [8][9][10] The recently developed diblock copolymer D-α-tocopheryl polyethylene glycol 1000 succinate-b-poly(ε-caprolactone-ran-glycolide) (TPGS-b-(PCL-ran-PGA) [hereafter, referred to as PLGA-TPGS]) has received special attention as a promising antimicrobial agent, due to its good biocompatibility and biodegradability. 7 Therefore, the synthesis of uniform PLGA-TPGS copolymer NPs (PLGA-TPGS NPs) with specific requirements in terms of size, shape, and physical and chemical properties is of great interest in the development of new drugs.…”
mentioning
confidence: 99%
“…7 Therefore, the synthesis of uniform PLGA-TPGS copolymer NPs (PLGA-TPGS NPs) with specific requirements in terms of size, shape, and physical and chemical properties is of great interest in the development of new drugs. 8,9 A variety of studies [8][9][10] have shown they have good biocompatibility and biodegradability and excellent targeted drug delivery, but the antifungal effects of AMB-loaded PLGA-TPGS NPs (AMBNPs) are mostly unknown. In this study, AMB-NPs were synthesized, and their antifungal effects on the Candida spp.…”
mentioning
confidence: 99%
“…Recently, polylactide NPs containing basic acid were more effective than microemulsions in an in vivo hamster model of VL [16]. Other example includes AmBloaded in poly (ε-caprolactone) NPs [17] or in mannose-anchored, PLGA NPs for the efficient delivery of AmB to macrophages [18].…”
Section: Introductionmentioning
confidence: 99%
“…102 With regard to the active targeting approach, mannosebearing PLGA nano/microparticles have been designed to further improve macrophage targeting of antileishmanial agents. Mannose-grafted PLGA nanoparticles, with and without a PEG spacer, are reported to target AmpB; 103 the presence of PEG spacer resulted in a more efficient inhibition of parasites in comparison to both the one without spacer and the free drug. Furthermore, both drug-polymer interaction and drug miscibility in the polymer affect the drug content of polymer nanoparticles.…”
mentioning
confidence: 99%
“…However, in the engineered version of polymer nanoparticles, in which mannose was directly linked to PLGA (M-PNPs) or to the edge of PEG (M-PEG-PNPs), an increased entrapment efficiency was observed, probably due to the higher drug-polymer miscibility, permitting the enhanced drug incorporation. 103 The significant rise in drug content in M-PNPs and M-PEG-PNPs might be due to the stronger drug-polymer interaction (between the hydroxyl group of mannose and PEG and the amine group of AmpB) and to the high miscibility in the case of amphiphilic AmpB. Another study suggested that the acidic end-group of PLGA is responsible for drug incorporation and that increased chain length may increase the drug-polymer interactions, leading to improved drug incorporation efficiency.…”
mentioning
confidence: 99%